2004
DOI: 10.1002/bdrb.10055
|View full text |Cite
|
Sign up to set email alerts
|

Chemically induced supernumerary lumbar ribs in CD‐1 mice: Size distribution and dose response

Abstract: Supernumerary ribs (SNR) of differing sizes are commonly observed in rodent developmental toxicity studies, and the significance of treatment-related increases in SNR in standard studies has been contentious. We induced dose-related increases in SNR in fetal CD-1 mice by treating on gestation days 7-8 with benomyl (BEN; 0, 75, 150 mg/kg/d), dinoseb (DIN; 0, 30, 50 mg/kg/d); 2-methoxyethanol (2-ME; 0, 75, 150 mg/kg/d), or valproic acid (VPA; 0, 125, 250 mg/kg/d). Incidences of SNR were 9.3-27.6% in controls and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…The authors suggested that supernumerary ribs are indicative of basic alterations in the development of the axial skeleton (Branch et al, 1996). A similar study conducted by Rogers et al (2004) revealed a dose-related increased incidence of mouse fetuses with supernumerary ribs following maternal administration of dinoseb in NaOH at 50 mg/kg bw/day on GDs 7-8 and suggested that increased incidence of supernumerary ribs in fetuses is toxicologically significant. Skeletal anomalies such as sternum or vertebral centrum defects and fused ribs were also detected in fetuses of mice given dinoseb on GDs 7-8 at 50 mg/kg bw/day in NaOH.…”
Section: Gavage Studies In Micementioning
confidence: 87%
See 4 more Smart Citations
“…The authors suggested that supernumerary ribs are indicative of basic alterations in the development of the axial skeleton (Branch et al, 1996). A similar study conducted by Rogers et al (2004) revealed a dose-related increased incidence of mouse fetuses with supernumerary ribs following maternal administration of dinoseb in NaOH at 50 mg/kg bw/day on GDs 7-8 and suggested that increased incidence of supernumerary ribs in fetuses is toxicologically significant. Skeletal anomalies such as sternum or vertebral centrum defects and fused ribs were also detected in fetuses of mice given dinoseb on GDs 7-8 at 50 mg/kg bw/day in NaOH.…”
Section: Gavage Studies In Micementioning
confidence: 87%
“…In mice, gavage dosing of dinoseb during organogenesis induced skeletal variations and growth retardation at or above maternally toxic levels (26-50 mg/kg bw/day) (Branch et al, 1996;Kavlock et al, 1985). Teratogenic effects were observed without maternal toxicity at 50 mg/kg bw/day by gavage in CD-1 mice (Rogers et al, 2004). Doses of dinoseb in rats during organogenesis induced skeletal variations and growth retardation at maternally toxic levels (8.0-20 mg/kg bw/day) by gavage and (6.52-15 mg/kg bw/day) by feeding (Giavini et al, 1986;Matsumoto et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations